Assessment of passenger long-term vibration discomfort: a field study in high-speed train environments. Issue 4 (3rd April 2022) - Peng, Yong; Wu, Zhifa; Fan, Chaojie; Zhou, Jiahao; Yi, Shengen; Peng, Yuexiang; Gao, Ke
Abstract: This study revealed the mechanism of long-term passenger vibration discomfort in high-speed trains and proposed a novel evaluation model to assess it, while the most popular international standard ISO 2631-1 is unsuitable. Here, a field test was conducted to investigate the long-term passenger vibration comfort in high-speed trains under different operation environments by the measurement of the whole-body vibration (WBV) and the subjective ratings of passenger comfort. During the whole sitting period of high-speed train passengers, the phenomena 'compensatory degradation' and 'discomfort accumulation' were found, which meant that the brief termination of vibration cannot fundamentally alleviate passenger vibration comfort. And the vibration comfort can be evaluated by the product of exposure time and the novel vibration acceleration index we proposed. Meanwhile, high-speed trains with higher velocities or running in tunnel environments have higher frequency-weighted WBV amplitude than open-air and lower velocities, which caused more vibration discomfort of passengers. Practitioner Summary: This field study provided data support for ensuring the occupational health of train drivers whose work routes involve a large number of tunnels and improving passenger vibration comfort. Meanwhile, a novel idea was provided for evaluating the vibration comfort of passengers who prolonged exposure to low-amplitude environments.